Conducta obstétrica en multípara de 26 Años con hiperémesis gravídica. - Delgado Zambrano, Joselyn Tatiana (2021)
“Hyperemesis gravidarum is defined as excessive and persistent nausea and vomiting, a condition that results in hydroelectrolytic imbalance, weight loss, ketosis, and muscle wasting. It is estimated that 1 to 5% of cases require hospitalization and, furthermore, if it occurs in the first pregnancy, its recurrence in subsequent pregnancies is more likely”. (Dulay, 2020). The purpose of the present case is to know the development based on the obstetric conduct taken by the treaters in a 26-year-old multiparous patient who is going through a clinical picture of hyperemesis gravidarum, which will determine the scope of the stabilization and resolution of the problem with in order to train the new generations of health professionals on the management of such pathology. As relevant data of the case, it can be highlighted that the patient suffered a weight loss of approximately 17.7% of the value that should have been normal, in addition to electrolyte imbalance and dehydration. The management of the patient was carried out following the protocol, which is based on management with antiemetics to stop vomiting and parenteral and oral rehydration. All this in order to get the pregnancy to term, since it was not in its last weeks, therefore the risk of fetal viability was evident in the face of a bad procedure or a late intervention of the problem.